Does a Combination Pill of Antihypertensive Drugs Improve Medication Adherence in Japanese?: A Randomized Controlled Trial - Matsumura, Kiyoshi; Arima, Hisatomi; Tominaga, Mitsuhiro; Ohtsubo, Toshio; Sasaguri, Toshiyuki; Fujii, Koji; Fukuhara, Masayo; Uezono, Keiko; Morinaga, Yuki; Ohta, Yuko; Otonari, Takatoshi; Kawasaki, Junya; et al. (Circulation Journal, 2012)
Background: In order to achieve target blood pressure levels to prevent cardiovascular disease, combination therapy of antihypertensive drugs is often required, although it is thought that requiring a patient to take many different pills would reduce adherence to the medication regimen. Whether antihypertensive treatment with a single pill combining antihypertensive drugs would improve medication adherence and blood pressure control was investigated. Methods and Results: A total of 207 hypertensive subjects were randomly assigned to a combination pill group (losartan 50mg/hydrochlorothiazide 12.5mg; n=103) or a control group (an angiotensin receptor blocker and a thiazide diuretic; n=104). Medication adherence was evaluated by pill counts at 1, 3, and 6 months after randomization. The mean adherence rates over 6 months were not different between the 2 groups: 98% in the combination pill group and 98% in the control group. Moreover, the 2 groups included similar numbers of subjects with relatively poor adherence rates (<90%) in each treatment period. The mean blood pressures over the 6-month treatment period were not different between the groups: 131/75mmHg in the combination pill group and 130/75mmHg in the control group (P=0.84/0.96). Conclusions: There were no appreciable effects of the combination pill of antihypertensive drugs on medication adherence or blood pressure control in Japanese patients over a 6-month period. (Circ J 2012; 76: 1415-1422)